Inclusion body myositis: Update on the diagnostic and therapeutic landscape - Naddaf, Elie (Frontiers in Neurology, 2022)
Inclusion body myositis (IBM) is a progressive muscle disease affecting patients over the age of 40, with distinctive clinical and histopathological features. The typical clinical phenotype is characterized by prominent involvement of deep finger flexors and quadriceps muscles. Less common presentations include isolated dysphagia, asymptomatic hyper-CKemia, and axial or limb weakness beyond the typical pattern. IBM is associated with marked morbidity as majority of patients eventually become wheelchair dependent with limited use of their hands and marked dysphagia. Furthermore, IBM mildly affects longevity with aspiration pneumonia and respiratory complications being the most common cause of death. On muscle biopsy, IBM is characterized by a peculiar combination of endomysial inflammation, rimmed vacuoles and protein aggregation. These histopathological features are reflective of the complexity of underlying disease mechanisms. No pharmacological treatment is yet available for IBM. Monitoring for swallowing and respiratory complications, exercise and addressing mobility issues are the mainstay of management. Further research is needed to better understand disease pathogenesis and identify novel therapeutic targets.